Extraction of Total RNA from Leaves of Eucalyptus and Other Woody and Herbaceous Plants Using Sodium Isoascorbate - Y. Suzuki; T. Hibino; T. Kawazu; T. Wada; T. Kihara; H. Koyama (BioTechniques, 2003)
Rapid extraction of total RNA from Eucalyptus leaves is difficult due to the high content of polyphenolics and polysaccharides. A rapid and simple method was developed by using an extraction buffer containing sodium isoascorbate at a concentration of 500 mM. This method consisted of one or two chloroform extractions, one acid guanidium-phenol-chloroform extraction, and isopropanol precipitation alone. The yields of the RNA fractions were 246–1750 μg/g fresh weight when leaves of Eucalyptus, five other woody plants, and four herbaceous plants were used as samples. The contamination of the RNA fractions by proteins and polysaccharides was very limited as judged spectrophotometrically. When the RNA fractions were subjected to agarose gel electrophoresis, intact rRNA bands were detected. The RNA fractions could be used for RT-PCR. These results indicate that our new method achieves a simple and rapid preparation of high-quality RNA from leaves of Eucalyptus and other plant species.